2015
DOI: 10.14254/2071-8330.2015/8-1/8
|View full text |Cite
|
Sign up to set email alerts
|

Model of the loan process in the context of unrealized income and loss prevention

Abstract: Currently, in the banking sector of the economically developed countries is possible to monitor the trend of high liquidity and the low volume of credit nancing of Small and Medium-sized Enterprises (SMEs). is situation is far from ideal because the banks are losing potential revenue and the SME segment within appropriate extent cannot nance its business objectives through bank loans. e aim of the paper was to propose a model for a comprehensive assessment of the credit worthiness of the client and retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Researches dealing with the soft information generation and bank lending efficiency argue that the soft information collection and careful examination of the information can increase the lending efficiency of the bank that can positively affect the small business access to credit (D'Aurizio et al, 2015). On the other hand, empirical results show that commercial banks can improve the credit rating model by including the relationship lending qualitative (soft) information of the borrower in the rating process, and that focus only on the hard financial information can be misleading (Dolezal et al, 2015) However, literature review shows that banking relationship and soft information generation can be affected by various factors including the type of bank ownership. It is found that information from the lending relationship are usually local in nature and, as a result, it is possible for the local banks to gather this proprietary information much better than for the distant banks (Jimenez et al, 2006).…”
Section: Banks Ownership and Relationship Lendingmentioning
confidence: 99%
“…Researches dealing with the soft information generation and bank lending efficiency argue that the soft information collection and careful examination of the information can increase the lending efficiency of the bank that can positively affect the small business access to credit (D'Aurizio et al, 2015). On the other hand, empirical results show that commercial banks can improve the credit rating model by including the relationship lending qualitative (soft) information of the borrower in the rating process, and that focus only on the hard financial information can be misleading (Dolezal et al, 2015) However, literature review shows that banking relationship and soft information generation can be affected by various factors including the type of bank ownership. It is found that information from the lending relationship are usually local in nature and, as a result, it is possible for the local banks to gather this proprietary information much better than for the distant banks (Jimenez et al, 2006).…”
Section: Banks Ownership and Relationship Lendingmentioning
confidence: 99%
“…Despite the fact that non-bank lending supported the growth of capital ratios, this indicator had a negative correlation with ROA and could lead to an increase in risk loans. Doležal et al (2015) note that credit risk for SMEs is an actual theoretical, scientific and practical task for research for minimizing the credit risk of commercial banks and increasing their efficiency. The results of their research showed that there is a high probability of improving the credit process for small and medium-sized businesses segment, which is an important factor in overall economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These measures include the state support of the means of export financing. Export financing of SMEs is a major problem which determines the current and future performance of these companies, bringing the potential growth of the company, its stability and future (Doležal, 2015).…”
Section: Introductionmentioning
confidence: 99%